Resilient leadership in female principals: a case study of a Chinese female school leader - Yin, Hongjie; Liu, Jia (Frontiers in Education, 2026)
The educational transformation in China has introduced unprecedented complexity and uncertainty into school organizations, presenting unique challenges and opportunities for educational leadership. This qualitative study single-case study explores the antecedents and development of resilient leadership by examining the case of a female vice-principal at a higher vocational college, utilizing three in-depth interviews supplemented by a 2-months period of naturalistic observation. The findings underscore the importance of individual traits, past successes, and external factors in nurturing resilient leadership among female principals. By integrating the trait and behavioral perspectives of resilience theory, female resilient leadership can be categorized into three domains in Chinese contexts: perceptiveness and planning, resistance and adaptability, and inspiration and growth potential. Drawing on resource conservation theory, the study delineates the development of female resilient leadership in schools and provides recommendations for enhancing leadership practice.